Outcomes Following Oncoplastic Reduction Mammoplasty: A Systematic Review. (May 2016) - Piper, Merisa L.; Esserman, Laura J.; Sbitany, Hani; Peled, Anne Warren
Abstract : Background: Reconstruction of partial mastectomy defects with oncoplastic approaches has become increasingly popular as a strategy for improving aesthetic outcomes and extending the option of breast conservation therapy. However, interpretation of reported oncologic outcomes and postoperative complications has been challenging because of limited data and significant variability in surgical technique and degree of tissue rearrangement. Methods: Studies describing oncoplastic mammoplasty or partial mastectomy reconstruction were identified from the MEDLINE and Cochrane databases. Only studies reporting the use of oncoplastic reduction mammoplasty techniques with significant breast parenchymal rearrangement were included for analysis. Primary outcomes assessed were postoperative complications and oncologic outcomes, including local recurrence rates and need for re-excision or completion mastectomy. Results: Seventeen articles met the inclusion criteria, representing 1324 oncoplastic cases. Reported follow-up ranged from 20 to 73 months. Of the 12 studies with at least 2 years' mean/median follow-up, the pooled local-regional recurrence rate was 3.1%. Fifteen articles reported re-excision and completion mastectomy rates (3.5% and 3.7%, respectively). Twelve articles reported postoperative complications. Overall, 4.6% of patients had wound dehiscence, 4.3% developed fat necrosis, 2.8% developed an infection, 0.9% had either partial or total nipple necrosis, and 0.6% had seromas. Conclusions: Partial mastectomy reconstruction with oncoplastic reduction techniques is associated with high rates of successful breast conservation and low rates of required re-excisions, likely due to the ability to take wide tumor margins without compromising aesthetic outcome. Future studies should consistently report complications, recurrences, and patient-reported outcomes to improve our ability to evaluate the use of this technique.